Shear-thinning conductive chitosan-based nano-hybrid hydrogels by host–guest supramolecular assembled poly ethylene glycol and reduced graphene oxide dual cross-linkers - Javad Saberi; Fathallah Karimzadeh; Jaleh Varshosaz; Sheyda Labbaf (Biomedical Engineering Advances)
Here, a chitosan-based shear-thinning and conductive nano-hybrid hydrogel is developed based on self-assembled host-guest (HG) supramolecular interaction between beta-cyclodextrin modified chitosan (Host, Cs-CD) and adamantane grafted polyethylene glycol (Guest, PEG-AD) and secondary cross-linking with reduced graphene oxide (rGO). The concentration of HG macromers handled the rheological and mechanical behavior of the forming hydrogel, the ratio of the guest macromer, and the amount of rGO. Dual cross-linking hydrogel (macromers concentration=10 wt%) H:G = 1:2 (CPH 102G3) had the highest mechanical strength and toughness (about 3-folds) compared to the (10 wt%) 1:2 hydrogel (CPH 102). Also, (15 %wt) 1:2 Hydrogel (CPH 152) had mechanical strength and toughness of about 6-folds compared to (10 wt%) 1:4 hydrogel (CPH 104). The electro-conductivity of Cs-PEG/rGO nano-hybrid hydrogel was between 3.5 to 6.55 mS.cm-1 and within the myocardial tissue conductivity range. The swelling ratio and degradation rate of hydrogels were also investigated. CPH 102G3 displayed lower than 45 % weight loss after 15 days of immersion in a phosphate buffer saline solution. Finally, all hydrogel samples demonstrated non-cytotoxicity 24 h post-seeding. After 120 h, cell proliferation was observed. In conclusion, Cs-PEG/rGO hydrogel promises to emerge as an injectable scaffold with controllable properties for electroactive tissue engineering applications.